2015
DOI: 10.1242/jcs.156950
|View full text |Cite
|
Sign up to set email alerts
|

The integrin expression profile modulates orientation and dynamics of force transmission at cell–matrix adhesions

Abstract: Integrin adhesion receptors connect the extracellular matrix (ECM) to the cytoskeleton and serve as bidirectional mechanotransducers. During development, angiogenesis, wound healing and cancer progression, the relative abundance of fibronectin receptors, including integrins a5b1 and avb3, changes, thus altering the integrin composition of cell-matrix adhesions. Here, we show that enhanced avb3 expression can fully compensate for loss of a5b1 and other b1 integrins to support outside-in and inside-out force tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 26 publications
9
62
0
1
Order By: Relevance
“…α5β1 is generally considered to be the β1-based integrin that drives invasive carcinoma migration in FN-rich matrices4647. Indeed, the ability of this integrin to sense substrate rigidity and generate traction forces for migration in FN environments has been extensively studied (typically on plasma FN) in fibroblasts and in various tumour cells4748495051. Viewed in this context, our findings that blocking α9β1, rather than α5β1, efficiently phenocopy the effect of pan-β1-blocking antibodies on cohort migration are unexpected and hence thought provoking.…”
Section: Discussionmentioning
confidence: 99%
“…α5β1 is generally considered to be the β1-based integrin that drives invasive carcinoma migration in FN-rich matrices4647. Indeed, the ability of this integrin to sense substrate rigidity and generate traction forces for migration in FN environments has been extensively studied (typically on plasma FN) in fibroblasts and in various tumour cells4748495051. Viewed in this context, our findings that blocking α9β1, rather than α5β1, efficiently phenocopy the effect of pan-β1-blocking antibodies on cohort migration are unexpected and hence thought provoking.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Balcioglu HE et al 14 . reported that αvβ3 integrin-mediated adhesion enables FA assembly even at low matrix stiffness, while traction force magnitude remains unvaried.…”
Section: Discussionmentioning
confidence: 99%
“…The traction forces are dependent on the integrin subtype. In particular, α 5 β 1 and α V β 3 mediate cellular tractions differently [Roca‐Cusachs et al., ; Rossier et al., ; Balcioglu et al., ]. The activation of β 1 integrin by increased FN density or Mn 2+ increases traction forces in fibroblasts.…”
Section: Textmentioning
confidence: 99%